A Formação Permanente Relacional na Educação Física Escolar - Silva, Maria Eleni Henrique da (2011)
This thesis presents a research-intervention in the process of continuing education of Physical Education (PE) teachers from the Public Education Schools in Fortaleza, Ceará State, subsidized by/based on the Eco-Relational Perspective (PER). The research presents evidences about the need to rethink the usual education programs in Physical Education/ PE. We have noticed in recent years, the increase in continuing education programs within the Physical Education/PE, in order to improve teachers' pedagogical action in school. However, these programs are still designed according to the classical perspective, even if some elements inclusions that indicate changes can be observed, in a critical and reflective perspective. Thus, with the aim of contributing to a continuing education in tune with the critical do-act-feelthink in establishing a proposal in partnership with the teachers and also considering their needs, from the reflection and reframing of the pedagogical practices, which aims to 'Relational Continuing Education' as a possibility. The paper analyzes the contributions that the Eco-Relational Perspective provides to the continuing education of Physical Education/PE teachers, considering the improvement of pedagogical practice. It also sought to describe the course of experienced training; verify the changes resulting from the process, outline the pedagogical practice of Physical Education (PE) teachers, linked to research, during and after this training, and reveal the impact that it offers and its consequences for pedagogic practice in Physical Education/PE. The main theoretical contributions came from Freire s proposal, together with Figueiredo s Eco-Relational Perspective studies. We believe that the permanent training presents favorable results to improve the professional and personal teachers practice, guided by critical reflection, the partner relationship, the dialogue, affection, experience, as opposed to the classical logic of continuing education. The prime methodological approach was developed along the lines of Critical-Collaborative Action Research. The researchintervention was performed by the project: "Teacher Training and Qualification: knowledge in weaving movement for the teaching of Physical Education," with a proposal for an extension course, with a learner group composed by 50 Physical Education teachers. The course had a workload of 200 hours. We used questionnaires, interviews, audio and video of the courses, written records and photographic materials produced by the teachers as instruments for data collection. We also worked this data, especially through the content analysis. We elaborated for the results exposition of the four analysis categories: the concepts of continuing education; the reflexivity in the path of relational continuing education; the experience in relational continuing education; the characterization of teachers pedagogical practice and the contributions of continuing education in the way of change. The Eco- Relational perspective, wherein the Relational Continuing Education enhanced the teaching qualification and contributed to meaningful changes in Physical Education teaching practice. We conclude that this continuing education carries a set of principles, values and procedures that take into account the priority attention relations and pedagogical practices of teacher and reflection on the training route, points to the foundational aspects of collaborative learning in relational dynamics via formation of the learner group, which makes group-author-partner in the way of changes that lay beyond the pedagogical practices.